Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fphy.2022.1005447
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic flow of casson nanofluid over a vertical riga plate with ramped wall conditions

Abstract: The present study aims to investigate the Casson nanofluids flow theoretically over a vertical Riga plate. The temperature and concentration with ramped and isothermal wall conditions are considered. Moreover, the fluid is considered electrically conducted. Concrete is considered as a base fluid while clay nanoparticles are added to it. The present flow regime is formulated in terms of a system of partial differential equations. Using dimensionless variables, the system of equations with the imposed boundary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In this portion, we used excellent Maple packages and BVP [mid-rich] tackles for examining the system of nonlinear differential Eqs. (17) to (19). The BVP [mid-rich] methodology uses mathematics to tackle boundary value constraints.…”
Section: Resultsmentioning
confidence: 99%
“…In this portion, we used excellent Maple packages and BVP [mid-rich] tackles for examining the system of nonlinear differential Eqs. (17) to (19). The BVP [mid-rich] methodology uses mathematics to tackle boundary value constraints.…”
Section: Resultsmentioning
confidence: 99%
“…Choi and Eastman (1995) studied thermal conductivity of fluids with nanoparticles. Pramanik (2014) Casson nanofluid flow theoretically over a vertical Riga plate was studied by Khan et al (2022). They observed that increase in skin-friction caused a rigid compaction of the materials and improves the tensile strength of the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Mu et al [12] investigated multi-attribute DM (MADM) relying on interval-valued Pythagorean FS. Researchers can expand the theory of FS, IvFS to various other theories such as [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%